Adolescent Diet Quality and Cardiovascular Disease Risk Factors and Incident Cardiovascular Disease in Middle‐Aged Women. Issue 12 (20th December 2016) - Dahm, Christina C.; Chomistek, Andrea K.; Jakobsen, Marianne Uhre; Mukamal, Kenneth J.; Eliassen, A. Heather; Sesso, Howard D.; Overvad, Kim; Willett, Walter C.; Rimm, Eric B.; Chiuve, Stephanie E.
Abstract : Background: Primary prevention of cardiovascular disease (CVD) focuses on treatment of risk factors, including hypercholesterolemia, hypertension, and type 2 diabetes mellitus. We investigated whether a healthy diet in adolescence prevents development of clinical risk factors or incidence of CVD in adulthood. Methods and Results: We examined the time to the first development of ≥1 clinical risk factor (hypercholesterolemia, hypertension, or type 2 diabetes mellitus) or CVD in relation to a high school Alternative Healthy Eating Index (HS‐AHEI) within the Nurses' Health Study II. Among those who completed a food frequency questionnaire about their high school diet and adult diet (mean age 42 years), 27 406 women free of clinical risk factors and 42 112 women free of CVD in 1998 were followed to June 2011. Hazard ratios (HRs) and 95% CIs were adjusted for potential confounders in high school and adulthood. We documented 11 542 first diagnoses of clinical risk factors and 423 CVD events. The HS‐AHEI was associated with a lower rate of risk factors (HR highest versus lowest quintiles 0.82; 95% CI, 0.77–0.87 [ P trend <0.001]), was inversely associated with risk of developing ≥1 clinical risk factor in women with a low, medium, and high AHEI score during adulthood (HR high HS‐AHEI/high adult AHEI versus low/low 0.79 [95% CI, 0.74–0.85]), but was not statistically significantly associated with incident CVD. Conclusions: A healthy diet during adolescence is associated with lower risk of developing CVD risk factors. As diet tracks throughout life, and adult diet prevents CVD, healthy dietary habits that begin early are important for primordial prevention of CVD.